Field testing of a digital health information system for primary health care: A quasi-experimental study from India. (September 2020) - Faujdar, Dharamjeet S.; Sahay, Sundeep; Singh, Tarundeep; Kaur, Manmeet; Kumar, Rajesh
Highlights: Integrated population and patient-centric model for the development of Digital Health system. Living lab concept for designing integrated health information system for primary health care. Addressing multiple functions of primary health care using digital health system. Quasi-experimental study to assess effectiveness of integrated health information system. Improvement in primary health care services and health outcomes with integrated health information system. Abstract: Introduction: Information and Communication Technologies (ICTs) are acknowledged as vital tools to strengthen Primary Health Care (PHC) in low- and middle-income countries (LMICs). However, these technologies have been used only for selected services. Moreover, there is limited evidence on how effective these interventions are in improving comprehensive primary health care in LMICs. Therefore, we developed an integrated digital solution and field-tested its impact on PHC services in an urban community of India. Methods: An integrated health information system for primary health care (IHIS4PHC) was designed on a free and open source digital platform which provided multiple features for registration of population and tracking for promotive, preventive, and curative health services (e.g. Antenatal Care, Immunization, TB, Malaria, and Hypertension Treatment etc.), and for generation of aggregate reports for real-time monitoring. The IHIS4PHC was implemented in an urban health centre of Chandigarh (India) which catered to about 25, 000 population. A quasi-experimental study design was chosen for analysing the impact of IHIS4PHC on PHC services. Household sample surveys were conducted at baseline and endline in the intervention and comparison community to estimate the coverage of selected health indicators using standard questionnaires. Difference-in-difference method with adjusted generalised estimating equation was used for the assessment of the net impact of IHIS4PHC. Results: In relation to the comparison community, statistically significant (p < 0.05) increase was observed at the IHIS4PHC implementing centre in primary health care adequacy (7.2 %), and in the care-seeking behaviour for chronic illness (16.5 %). Improvements were also noticed in other health indicators such as mean blood pressure, adherence to antihypertensive medication, intake of dietary salt by hypertensives, intention to quit tobacco, and vitamin A supplementation. Conclusions: The digital IHIS4PHC design was found to be effective in improving PHC-based health services. Therefore, IHIS4PHC like digital solutions should be considered for strengthening PHC services in LMICs.